Design and Implementation of Public Service web-based Information System Using RESTful API and Firebase: A Case Study in Takalar Education Office - Fathahillah, Fathahillah; Muh. Yahya; Amiruddin, Amiruddin (Cita konsultindo, 2025)
Effective and transparent public service is a key indicator of good governance, especially in the education sector. Initial findings revealed that the administrative services at the Takalar District Education Office were still manual, unintegrated, and lacked accessible information. This study aims to develop a centralized, transparent, and easily accessible public service system available on web platforms. The research employed a Research and Development (R&D) approach with development stages synthesized from various instructional models, including ADDIE, 4D, Borg and Gall, Prototyping, and Dick & Carey. The stages included needs analysis, system design, prototype development, expert validation, user testing, and limited implementation. Data were gathered through observation, interviews, and questionnaires administered to administrative staff and teachers. The final product was administrative service system website. System evaluation based on ISO/IEC 25010 demonstrated validity across all standards aspects: functionality, efficiency, compatibility, usability, reliability, security, maintainability, and portability. Based on the development and testing software results confirm that the system is functional, user-friendly, and effective as a digital public service solution for improving administrative performance in the education sector.